Altered functional properties of the codling moth Orco mutagenized in the intracellular loop-3 - Yuriy V. Bobkov (Nature Portfolio, 2021)
Abstract Amino acid substitutions within the conserved polypeptide sequence of the insect olfactory receptor co-receptor (Orco) have been demonstrated to influence its pharmacological properties. By sequence analysis and phylogenetic investigation, in the Lepidopteran subgroup Ditrysia we identified a fixed substitution in the intracellular loop-3 (ICL-3) of a conserved histidine to glutamine. By means of HEK293 cells as a heterologous system, we functionally expressed Orco from the Ditrysian model Cydia pomonella (CpomOrco) and compared its functional properties with a site-directed mutagenized version where this ICL-3-glutamine was reverted to histidine (CpomOrcoQ417H). The mutagenized CpomOrcoQ417H displayed decreased responsiveness to VUAA1 and reduced response efficacy to an odorant agonist was observed, when co-transfected with the respective OR subunit. Evidence of reduced responsiveness and sensitivity to ligands for the mutagenized Orco suggest the fixed glutamine substitution to be optimized for functionality of the cation channel within Ditrysia. In addition, contrary to the wild type, the mutagenized CpomOrcoQ417H preserved characteristics of VUAA-binding when physiologic conditions turned to acidic. Taken together, our findings provide further evidence of the importance of ICL-3 in forming basic functional properties of insect Orco- and Orco/OR-channels, and suggest involvement of ICL-3 in the potential functional adaptation of Ditrysian Orcos to acidified extra-/intracellular environment.